2014
DOI: 10.1021/ac501586d
|View full text |Cite
|
Sign up to set email alerts
|

Near Infrared (NIR) Strong Field Ionization and Imaging of C60 Sputtered Molecules: Overcoming Matrix Effects and Improving Sensitivity

Abstract: Strong field ionization (SFI) was applied for the secondary neutral mass spectrometry (SNMS) of patterned rubrene films, mouse brain sections, and Botryococcus braunii algal cell colonies. Molecular ions of rubrene, cholesterol, C31 diene/triene, and three wax monoesters were detected, representing some of the largest organic molecules ever ionized intact by a laser post-ionization experiment. In rubrene, the SFI SNMS molecular ion signal was ~4 times higher than in the corresponding secondary-ion mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…In a follow up study, Shard et al used an empirical expression to model the variations in secondary ion intensities as a function of the volume fraction of each component in a binary blend and defined a parameter to quantify the sign and magnitude of the matrix effect in blends 61 . Other approaches for semi‐quantitative analysis include metal‐assisted SIMS (MetA‐SIMS), where a thin metal is deposited on top of the material under analysis, 62,63 analysis of prominent ion signals from metallic cations, 64,65 and laser post‐ionization 66,67 …”
Section: Overview Of Tof‐simsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a follow up study, Shard et al used an empirical expression to model the variations in secondary ion intensities as a function of the volume fraction of each component in a binary blend and defined a parameter to quantify the sign and magnitude of the matrix effect in blends 61 . Other approaches for semi‐quantitative analysis include metal‐assisted SIMS (MetA‐SIMS), where a thin metal is deposited on top of the material under analysis, 62,63 analysis of prominent ion signals from metallic cations, 64,65 and laser post‐ionization 66,67 …”
Section: Overview Of Tof‐simsmentioning
confidence: 99%
“…61 Other approaches for semi-quantitative analysis include metal-assisted SIMS (MetA-SIMS), where a thin metal is deposited on top of the material under analysis, 62,63 analysis of prominent ion signals from metallic cations, 64,65 and laser post-ionization. 66,67 The large size of ToF-SIMS datasets can complicate analysis. ToF-SIMS datasets can include threedimensional spatial information and high-resolution mass spectra, similar to hyperspectral image maps.…”
Section: Challenges In Tof-sims Data Analysismentioning
confidence: 99%
“…The most prominent is m/z 530.5, a wax monoester previously discovered elsewhere. [29] In nature, wax monoesters have the ability to provide a protective function against bacterial infection and desiccation. Here, it is found to be a component of the sturdy and rigid extracellular matrix that is localized to the surface of the algal colony.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have reported that femtosecond-pulsed lasers operating in the strong field regime and in the IR spectrum greatly reduce photofragmentation and result in excellent sensitivity for a wide range of molecules. 15,16 Here, we take advantage of this laser configuration to employ LPI to characterize a binary mixture of multilayers of Irganox 1010 and Irganox 1098 similar to that investigated in the VAMAS study to examine the magnitude of matrix effects associated with the neutral desorption channel. With a primary ion beam of 20 keV C 60 , the results show that matrix effects are effectively overcome during molecular depth profiling and that the molecular ion intensity of Irganox is comparable to that observed using SIMS.…”
Section: ■ Introductionmentioning
confidence: 99%